2020
DOI: 10.4209/aaqr.2019.11.0574
|View full text |Cite
|
Sign up to set email alerts
|

BTEX Exposure Assessment and Inhalation Health Risks to Traffic Policemen in the Klang Valley Region, Malaysia

Abstract: Benzene, toluene, ethylbenzene, m,p-xylene, and o-xylene (collectively referred to as BTEX), which are prevalent in the ambient air of urban environments, potentially cause chronic health effects, particularly among outdoor workers. Aim of this study was to evaluate BTEX concentrations in the Klang Valley of Malaysia and assess the health risks to urban traffic police officers, whose duties include controlling the traffic flow and enforcing traffic laws. Air samples were collected with low-flow personal sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 85 publications
4
8
0
Order By: Relevance
“…Meanwhile, the TEQ value in the comparative dataset contributed about 66.7% variance of the risk output ( Figure 4 B). Similarly, the body weight of children in the comparative area had an antagonistic relationship (−0.19), which is consistent with health risk assessment studies [ 51 , 79 , 80 ].…”
Section: Resultssupporting
confidence: 87%
“…Meanwhile, the TEQ value in the comparative dataset contributed about 66.7% variance of the risk output ( Figure 4 B). Similarly, the body weight of children in the comparative area had an antagonistic relationship (−0.19), which is consistent with health risk assessment studies [ 51 , 79 , 80 ].…”
Section: Resultssupporting
confidence: 87%
“…Gasoline workers had health risks from BTEX chronic exposure and some workers had a higher than acceptable risk of BTEX exposure [ 5 , 6 ]. It was also shown that the lifetime cancer risk of exposure to benzene in Thai gasoline workers exceeded the acceptable limit [ 5 , 7 , 8 ] and this risk was similar to that found in the studies in Malaysia [ 9 , 10 ]. The health risks of working in hazardous zones at gasoline stations related to BTEX exposure are still not clear with regard to the contribution from sources of vaporization.…”
Section: Introductionsupporting
confidence: 69%
“…From the adverse-effect risk assessment findings on exposure to BTEX via inhaled air in working zones, it was found that there were five stations which had a high health risk value exceeding an acceptable limit (HI>1) for BTEX exposure. As a result, benzene exposure at five gasoline stations was assessed to be unacceptable with regard to human risk, which was supported by recent studies in Thailand [ 6 ] and Malaysia [ 9 , 10 ], which has similar climatic conditions to Thailand. The previous findings showed that an unacceptable risk (HQ>1) of benzene exposure at gasoline stations was related to their locations, i.e.…”
Section: Discussionmentioning
confidence: 72%
“…Muhammad et al (2012) recorded a relatively lower mean value of PM 2.5 at 22.33 ± 8.54 µg m -3 in a study among traffic police in Kuala Lumpur back in 2012. A current study by Fandi et al (2020) reported that extended exposure to benzene and ethylbenzene increases the risk of adverse health effects among traffic police.…”
Section: Exposure Level Among Traffic Police Personnelmentioning
confidence: 91%
“…Fandi et al (2018) Traffic police (KL) PM 10 The respiratory symptoms were significantly higher in the exposed group which they were 3.9, 4.1, and 3.5 times more likely to develop cough, wheezing, and breathlessness respectively. Fandi et al (2020) Traffic police (Klang Valley) Benzene, toluene, ethylbenzene, m,p-xylene, and o-xylene (BTEX)…”
Section: Pm 10mentioning
confidence: 99%